X-26=-41

Simple and best practice solution for X-26=-41 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-26=-41 equation:


Simplifying
X + -26 = -41

Reorder the terms:
-26 + X = -41

Solving
-26 + X = -41

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '26' to each side of the equation.
-26 + 26 + X = -41 + 26

Combine like terms: -26 + 26 = 0
0 + X = -41 + 26
X = -41 + 26

Combine like terms: -41 + 26 = -15
X = -15

Simplifying
X = -15

See similar equations:

| 11=(-4x-4)+x | | (x-3)(x-1)-48=0 | | 4(x+2)-4x-2=4 | | 6y^2+44y-90=0 | | (-1+45x)+(23x)=135 | | 7s-10=-3 | | 3-4r+2=2r-6(r-3) | | 80=-5(2x-4)-5x | | 2-7r+7=2r-9(r-1) | | -5x-2y=-14 | | 10t-3-t=3+9t | | -2+3x=-y | | -2(x+2)-5=-2x+1 | | -4+x=5 | | 6v=5.4 | | 6.5k+5-5.5k=14 | | x+4y=-26 | | x+1.25=-2.50 | | 5*(2x-3)=x(8-x) | | 12x+11=-13 | | 9.5=x+4.2 | | x(x+6)=24 | | 8x-3(x-5)=30 | | 12x+19=-17 | | -2d-7=11 | | 2x-10+4x+10=50 | | 10x+32=-18 | | X^2-21X+1=0 | | 8y-3=5(2y+2) | | 12x+13=-11 | | 3t^2-12t+4=0 | | 2+9x+8=46 |

Equations solver categories